ANALISIS PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS (Studi Kasus pada Perusahaan Sektor Perdagangan Eceran di Bursa Efek Indonesia Periode 2012-2015) - Fahmiwati, Nurul; Luhgiatno, Luhgiatno; Widaryanti, Widaryanti (JAB (Jurnal Akuntansi & Bisnis), 2017)
Financial distress is a condition where the financial company in a state of crisis or unhealthy. This study aims to analyze the Ratio of Financial Leverage, Liquidity, Sales Growth and Activity to Financial Distress.Â  This study have done at 23 Retail Trade Sector Companies in Indonesia Stock Exchange (IDX) during period 2012-2015. The population in this study are 23 companies of the retail sector listed on the Indonesian Stock Exchange period 2012-2015. Data collection method using purposive sampling method. The method of analysis using logistic regression analysis. The result shows that financial distress influenced by Financial leverage and activity ratio. The variables of liquidity and sales growth have no significant influence on the company's financial distress.Keywords: Financial Leverage, Liquidity, Sales Growth, Activity, and Financial Distress.